2022
DOI: 10.1371/journal.pone.0267050
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of clinician predictions of survival in the Prognosis in Palliative care Study II (PiPS2): A prospective observational study

Abstract: Background Prognostic information is important for patients with cancer, their families, and clinicians. In practice, survival predictions are made by clinicians based on their experience, judgement, and intuition. Previous studies have reported that clinicians’ survival predictions are often inaccurate. This study reports a secondary analysis of data from the Prognosis in Palliative care Study II (PiPS2) to assess the accuracy of survival estimates made by doctors and nurses. Methods and findings Adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Although all predicting tools for survival are insufficiently accurate in clinical use, the study still found high correlation between predicting tools and outcome. Stone et al (2022) further explored the accuracy of CPS in a large clinical study with 1833 patients in palliative care, 431 physicians and 777 nurses [36]. This latest article suggested that both professional groups were better than the chance of in survival prediction; especially, the performance of clinician was "very good" at predicting imminent death, not surprisingly corresponding to common understanding.…”
Section: Need For Objective Prediction Of Survivalmentioning
confidence: 99%
“…Although all predicting tools for survival are insufficiently accurate in clinical use, the study still found high correlation between predicting tools and outcome. Stone et al (2022) further explored the accuracy of CPS in a large clinical study with 1833 patients in palliative care, 431 physicians and 777 nurses [36]. This latest article suggested that both professional groups were better than the chance of in survival prediction; especially, the performance of clinician was "very good" at predicting imminent death, not surprisingly corresponding to common understanding.…”
Section: Need For Objective Prediction Of Survivalmentioning
confidence: 99%
“…Third, the median survival time was relatively short as a few weeks. The CPS may have been affected by the "horizon effect," which is a phenomenon whereby CPS is more accurate when death is more imminent [24] Fourth, various de nitions of the accuracy of CPS exist [25]. Thus, the factors associated with CPS accuracy may vary depending on which de nition is applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that predictions of death within the next 7 days were similarly accurate (79% and 77% for nurses and physicians, respectively). 3 The 3-day SQ is reported to have a sensitivity of 84%, specificity of 26%, PPV of 54%, negative predictive value (NPV) of 84% and overall accuracy of 59% ( N = 1411 patients with PPS ≤20%). 75 …”
Section: Prognosticating In Patients With An Expected Survival Of Daysmentioning
confidence: 98%
“… 13 One study reported limited evidence in support of this recommendation; however, although statistically significant, the magnitude of improvement was very small (accuracy of nurse prediction 55.2%, accuracy of doctor prediction 56.3%, accuracy of team prediction 57.5%). 14 There is also evidence to support the existence of the so-called ‘horizon effect’, the phenomenon whereby CPS is more accurate when death is more imminent, 3 , 15 although not all studies have observed this phenomenon. 16 …”
Section: Review Of Cpsmentioning
confidence: 99%